THE EFFECT OF CORPORATE VALUE AND CHARACTER TOWARD EMPLOYEE PERFORMANCE IN BANK BJB (The Indonesian Journal of Business Administration, 2019)
Character Building Education and Training that held by division of bjb University, until the mid of 2018, has already spent around 30 billion rupiahs thoroughly. The level of effectiveness for character building education and training can be measured. However, this measurement still does not exist until now. In addition, it is not possible to measure its effectiveness because character building education and training have been completed by all bank bjb employees. However, the implementation of character building education and training have been effective by testing the model values contained in the corporate value of bank bjb and testing the model of character building objectives that will be associated with employee performance. The model testing will be carried out to employees who have the best performance and non-best performance. There were 42 respondents who had filled out questionnaires for each best employee group and non-best employee group. the result of the questionnaire survey then it would be analyze using SEM PLS Statistic and explain the result with it.Keywords: Education and Training, Human Resources, People Knowledge Management.